Research progress on the role of MZB1 in immune regulation - Liu, Weiqi; Jiang, Kui; Jin, Minli; Chen, Xiaochi (Frontiers in Immunology, 2026)
MZB1 (Marginal Zone B and B1 Cell-Specific Protein), an endoplasmic reticulum-resident protein, has recently garnered significant attention for its role in immune regulation. As a critical modulator within various immune cells, MZB1 influences key processes such as cell differentiation, antibody production, and immune microenvironment dynamics. Despite advances in understanding, the precise mechanisms by which MZB1 contributes to immune homeostasis and dysregulation in pathological conditions remain incompletely defined. Emerging evidence highlights its involvement in tumor biology, inflammatory responses, and autoimmune diseases, positioning MZB1 as a potential therapeutic target. This review aims to synthesize current research findings on MZB1’s functions across different immune cell types, elucidate its interactions with other immune regulatory factors, and explore its impact on the tumor microenvironment and immune-mediated disorders.